1990
DOI: 10.1073/pnas.87.15.5988
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in NS2, a nonstructural protein of influenza A virus, extragenically causes aberrant replication and expression of the PA gene and leads to generation of defective interfering particles.

Abstract: Several consecutive undiluted passages of infectious virus are usually required to obtain defective interfering particles of influenza virus. In contrast, a reassortant (Wa-182) of influenza A/WSN, which we isolated, whose NS gene was replaced with the NS gene of A/Aichi, was readily converted to defective interfering form after only a single high-multiplicity infection. The defective interfering particles of Wa-182 were devoid of the PA gene (RNA segment 3) but possessed several species of subgenomic RNAs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 29 publications
(18 reference statements)
1
52
0
Order By: Relevance
“…We have, however, isolated an influenza A virus mutant, Wa-182, with a unique phenotype. We have demonstrated that after a single cycle of replication of Wa-182 at a high m.o.i., DI particles lacking the PA gene were predominantly produced (Odagiri & Tobita, 1990). In contrast, when the mutant was grown at low m.o.i., infectious progeny virus that retained the PA gene was produced.…”
Section: Introductionmentioning
confidence: 92%
“…We have, however, isolated an influenza A virus mutant, Wa-182, with a unique phenotype. We have demonstrated that after a single cycle of replication of Wa-182 at a high m.o.i., DI particles lacking the PA gene were predominantly produced (Odagiri & Tobita, 1990). In contrast, when the mutant was grown at low m.o.i., infectious progeny virus that retained the PA gene was produced.…”
Section: Introductionmentioning
confidence: 92%
“…Sequencing of DI RNAs showed that they were derived from genomic segments by internal deletion, and retained the terminal regions of the segment (Davis et al, 1980;Davis & Nayak, 1979;Duhaut & Dimmock, 1998, 2000Duhaut & McCauley, 1996;Hughes et al, 2000;Jennings et al, 1983;Moss & Brownlee, 1981;Nakajima et al, 1979;Nayak & Sivasubramanian, 1983;Nayak et al, 1982;Noble & Dimmock, 1995). As it became possible to determine the segment from which a DI RNA was derived, it became apparent that in many cases, their presence correlated with reduced amounts of the parent segment in virus particles (Akkina et al, 1984;Nakajima et al, 1979;Odagiri & Tobita, 1990;Ueda et al, 1980). Furthermore, this interference was shown to act at the level of packaging (rather than solely at the point of synthesis in cells) and also to affect the incorporation of the homologous segment in mixed infections of DI-containing and non-defective wild-type virus stocks (Duhaut & Dimmock, 2002;Duhaut & McCauley, 1996;Odagiri & Tashiro, 1997;Odagiri et al, 1994).…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 99%
“…These are truncated forms of genome segments which retain their ability to replicate and be packaged and which, due to their smaller size, out-compete full-length segments. Viruses containing DI RNAs arise in influenza A during high-multiplicity passage (von Magnus, 1954), particularly in certain genetic backgrounds (Nakajima et al, 1979;Odagiri & Tobita, 1990;Ueda et al, 1980). Sequencing of DI RNAs showed that they were derived from genomic segments by internal deletion, and retained the terminal regions of the segment (Davis et al, 1980;Davis & Nayak, 1979;Duhaut & Dimmock, 1998, 2000Duhaut & McCauley, 1996;Hughes et al, 2000;Jennings et al, 1983;Moss & Brownlee, 1981;Nakajima et al, 1979;Nayak & Sivasubramanian, 1983;Nayak et al, 1982;Noble & Dimmock, 1995).…”
Section: Genome Segmentation: a Mixed Blessingmentioning
confidence: 99%
“…In addition to the role of NS2/NEP in the export of vRNPs, it has been shown that a point mutation at position 32 in the NS2/NEP protein of the A/WSN/33 influenza virus Wa-182 results in the production of defective interfering (DI) particles lacking an intact PA gene after a single highmultiplicity cycle of infection (Odagiri & Tobita, 1990;Odagiri et al, 1994). Furthermore, a study in which an influenza A chloramphenicol acetyltransferase (CAT) reporter gene was used to assess RNA synthesis showed that the NS2/NEP protein inhibited RNA synthesis by reducing the levels of vRNA, cRNA and mRNA (Bullido et al, 2001).…”
Section: Introductionmentioning
confidence: 99%